Motor point heatmap of the calf - Elias Schriwer; Robin Juthberg; Johanna Flodin; Paul W. Ackermann (Journal of NeuroEngineering and Rehabilitation, 2023)
Abstract Background Contractions of muscles in the calf induced by neuromuscular electrical stimulation (NMES) may prevent venous thromboembolism, help rehabilitation and optimize strength training, among other uses. However, compliance to NMES-treatment is limited by the use of suboptimal stimulation points which may cause discomfort and less effectivity. Knowledge of where one is most likely to find muscle motor points (MP) could improve NMES comfort and compliance. Aims To anatomically map the MPs of the calf as well as to calculate the probability of finding a MP in different areas of the calf. Material and methods On 30 healthy participants (mean age 37 years) anatomical landmarks on the lower limbs were defined. The location of the four most responsive MPs on respectively the medial and lateral head of gastrocnemius were determined in relation to these anatomical landmarks using a MP search pen and a pre-set MP search program with 3 Hz continuous stimulation (Search range:4.0–17.5 mA). The anatomy of the calves was normalized and subdivided into a matrix of 48 (6 × 8) smaller areas (3 × 3 cm), from upper medial to lower lateral, in order to calculate the probability of finding a MP in one of these areas. The probability of finding a MP was then calculated for each area and presented with a 95% confidence interval. Results The MP heatmap displayed a higher concentration of MPs proximally and centrally on the calf. However, there were wide inter-individual differences in the location of the MPs. The highest probability of finding a MP was in area 4, located centrally and medially, and in area 29, located centrolaterally and around the maximum circumference, both with 50% probability (95% CI: 0.31–0.69). The second highest probability of finding MPs was in areas 9, 10, 16, proximally and medially, all with 47% probability (95% CI: 0.28–0.66). These areas 4, 9, 10, 16 and 29 exhibited significantly higher probability of finding motor points than all areas with a mean probability of 27% and lower (p < 0.05) The lateral and distal outskirts exhibited almost zero probability of finding MPs. Conclusions This MP heatmap of the calf could be used to expedite electrode placement and to improve compliance in order to receive consistent and enhanced results of NMES treatments.